Volunteer Training Series: Recognizing Young People - Georgene Bender; Tracy Tesdall; Judith Levings (EDIS)
Developing a sense of belonging is one of the Essential Elements of a positive youth development experience. Creating an inclusive environment in your 4-H club programs and activities can help you achieve this goal. Providing many forms of recognition for all, not just for those who excel in competition with other youth, also supports this sense of belonging. This 5-page fact sheet discusses recognition of participation, progress toward goals, standards of excellence, peer competition, and cooperation in the context of 4-H Clubs. Written by Georgene Bender, Tracy Tesdall, and Judith Levings, and published by the UF Department of 4-H Youth Development, November 2015.